Prospects for Detection of Extragalactic Stellar Black Hole Binaries in the Nearby Universe. (April 2015) - Benacquista, Matthew; Hinojosa, Jesus; Mata, Alberto; Belczynski, Krzysztof
Abstract: Stellar mass black hole binaries have individual masses between 10-80 solar masses. These systems may emit gravitational waves at frequencies detectable at Megaparsec distances by space-based gravitational wave observatories. In a previous study, we determined the selection effects of observing these systems with detectors similar to the Laser Interferometer Space Antenna by using a generated population of binary black holes that covered a reasonable parameter space and calculating their signal-to-noise ratio. We further our study by populating the galaxies in our nearby (less than 30 Mpc) universe with binary black hole systems drawn from a distribution found in the Synthetic Universe to ultimately investigate the likely event rate of detectable binaries from galaxies in the nearby universe.